EFFECTS AND APPLICATIONS OF CRYOEXPOSURE ASSOCIATED WITH HIGH INTENSITY ELECTROMAGNETIC FIELD IN HEALTH AND AESTHETICS: A REVIEW - Ruiz-Silva, Carlos; Moleiro, Daniela; R. Ruiz-Silva, Caroline (Health and Society, 2024)
Obesity has emerged as a global epidemic and represents a major risk factor for numerous chronic diseases, such as type 2 diabetes, cardiovascular disease, and cancer. Although adopting a healthy diet and regular exercise remain the cornerstones of weight management, recent research has revealed that cold exposure and associated muscle contractions can substantially contribute to weight loss. This article presents a comprehensive review of the physiological mechanisms that link cold exposure to weight loss, with a particular focus on the induction of browning and irisin production through pulsed electromagnetic field (PEMF) muscle stimulation technology, which uses alternating magnetic fields based on the law of electromagnetic induction to stimulate supramaximal muscle contractions with high magnetic flux density. The growing concern and interest in physical fitness, not only from an athletic but also aesthetic point of view, has driven the search for new methods and technologies that can aid in gaining muscle mass and tone. Recent studies have reported that 81% of respondents expressed dissatisfaction with their body image, even though 56% had a normal body mass index. Pulsed electromagnetic field (PEMF) muscle stimulation technology employs alternating magnetic fields based on the law of electromagnetic induction to induce supramaximal muscle contractions. PEMF generates impulses independent of brain function and at a frequency that does not allow muscle relaxation, thus characterizing tetanic contractions. Electrical currents and electromagnetism have long been used in physical therapy and rehabilitation, primarily for muscle strengthening. However, PEMF technology has emerged as a more effective and less invasive alternative for the patient, primarily intended for toning and strengthening muscle groups. In this study, we performed a comprehensive review of all available scientific articles indexed in PubMed and Web of Science over the past 20 years on this technology and its effects on skeletal muscle. We discuss the scientific evidence available from clinical studies and analyze the effects and possible mechanisms of action on muscle contraction.